Dr. Jekyll and Mr. Hyde? Physiology and Pathology of Neuronal Stress Granules - Jeon, Pureum; Lee, Jin A. (Frontiers in Cell and Developmental Biology, 2021)
Stress granules (SGs) are membraneless cytosolic granules containing dense aggregations of RNA-binding proteins and RNAs. They appear in the cytosol under stress conditions and inhibit the initiation of mRNA translation. SGs are dynamically assembled under stressful conditions and rapidly disassembled after stress removal. They are heterogeneous in their RNA and protein content and are cell type- and stress-specific. In post-mitotic neurons, which do not divide, the dynamics of neuronal SGs are tightly regulated, implying that their dysregulation leads to neurodegeneration. Mutations in RNA-binding proteins are associated with SGs. SG components accumulate in cytosolic inclusions in many neurodegenerative diseases, such as frontotemporal dementia and amyotrophic lateral sclerosis. Although SGs primarily mediate a pro-survival adaptive response to cellular stress, abnormal persistent SGs might develop into aggregates and link to the pathogenesis of diseases. In this review, we present recent advances in the study of neuronal stress granules in physiology and pathology, and discuss potential therapeutic approaches to remove abnormal, persistent SGs associated with neurodegeneration.